Concurrent and Predictive Criterion Validity of a Puppy Behaviour Questionnaire for Predicting Training Outcome in Juvenile Guide Dogs - Rebecca L. Hunt; Gary C. W. England; Lucy Asher; Helen Whiteside; Naomi D. Harvey (Animals, 2020)
Working dog organisations regularly assess the behaviour of puppies to monitor progression. Here, we tested the predictive validity (for predicting success in guide dog training) of a shortened version of a previously developed juvenile dog behaviour questionnaire (the refined puppy walker questionnaire, r-PWQ) and compared it with the Canine Behavioral Assessment and Research Questionnaire (C-BARQ). The r-PWQ is used by Guide Dogs UK, whereas the C-BARQ was designed for pet dogs and is used by some other guide dog schools internationally. A cohort of dogs aged eight months (n = 359) were scored concurrently on the r-PWQ and C-BARQ. Analogous traits between the questionnaires were evaluated for internal consistency and association with training outcome and compared for concurrent validity. The r-PWQ was associated with training outcome for five scales (r-Excitability, Trainability, Animal Chase, r-Attachment and attention seeking and Distractibility) and the C-BARQ for two scales (Excitability and Separation-related behaviour). There were significant correlations between analogous C-BARQ and r-PWQ trait scores (p < 0.001) except for Separation-related behaviour and questionnaire scales had similar internal consistencies. The r-PWQ may be more suitable to use with guide dog schools. However, due to the correlation between analogous scales (except for “Distractibility”) some scales could be substituted for one another when reviewing the behaviour of dogs between guide dog schools using different questionnaires.